2015
DOI: 10.1007/s40263-014-0223-x
|View full text |Cite
|
Sign up to set email alerts
|

mTOR Inhibition in Epilepsy: Rationale and Clinical Perspectives

Abstract: Despite a large number of available medical options, many individuals with epilepsy are refractory to existing therapies that mainly target neurotransmitter or ion channel activity. A growing body of preclinical data has uncovered a molecular pathway that appears crucial in many genetic and acquired epilepsy syndromes. The mammalian target of rapamycin (mTOR) pathway regulates a number of cellular processes required in the growth, metabolism, structure and cell-cell interactions of neurons and glia. Rapamycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 84 publications
3
60
0
1
Order By: Relevance
“…mTOR is involved in the regulation of a variety of physiological functions under normal conditions; dysregulation of these same mechanisms also contributes to the pathogenesis of many diseases, including epilepsy [40] . The mTOR pathway is hyperactive in some genetic and acquired epilepsies [40,41] , and inhibition of mTOR with rapamycin or an analog can delay or prevent seizure development [42,43] , the mechanisms have yet to be fully elucidated. In our study, we found that p70S6K 341 expression is increased in the acute, latent, and chronic stages of MTLE, and then we proved it in MTLE children, which is similar as in MTLE rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mTOR is involved in the regulation of a variety of physiological functions under normal conditions; dysregulation of these same mechanisms also contributes to the pathogenesis of many diseases, including epilepsy [40] . The mTOR pathway is hyperactive in some genetic and acquired epilepsies [40,41] , and inhibition of mTOR with rapamycin or an analog can delay or prevent seizure development [42,43] , the mechanisms have yet to be fully elucidated. In our study, we found that p70S6K 341 expression is increased in the acute, latent, and chronic stages of MTLE, and then we proved it in MTLE children, which is similar as in MTLE rats.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies suggest that most people with epilepsy will go into remission, while approximately onethird of epileptics continue to have seizures and are refractory to treatment with the currently available therapies, including antiepileptic drugs and surgical intervention [1,2] . About 70% of intractable epilepsy is temporal lobe epilepsy (TLE), with mesial TLE (MTLE) being the most common form.…”
Section: Introductionmentioning
confidence: 99%
“…mTORC1, sensitive to the inhibition by rapamycin, is regulated by the upstream Akt pathway in anabolic states and by the AMPK pathway in catabolic states [14]. mTOR signaling pathway has been found to influence the immune response [15], tumorigenesis [16], brain development [17], and epilepsy [14]. Regarding immune response, mTOR is implicated in the regulation of both innate and adaptive immune responses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Rapamycin (or sirolimus), the prototype mTOR inhibitor, enhanced the anti-inflammatory activities of regulatory T cells, decreased the production of proinflammatory cytokines and chemokines by macrophages and microglia, and thus attenuated secondary injury after focal ischemia in rats [18]. Several animal and human studies have shown that mTOR activation resulted in neuroexcitability, seizure, and epilepsy [14, 19], which encouraged researchers to use mTOR inhibitors in seizure therapy [14, 19, 20]. Everolimus is a second-generation rapamycin derivative.…”
Section: Introductionmentioning
confidence: 99%
“…The mTOR signaling cascade has also been implicated in epilepsy232425. Mutations in genes that regulate mTOR are associated with epilepsy-linked focal malformations of cortical development, including tuberous sclerosis complex262728.…”
mentioning
confidence: 99%